Types of habitat in the Universe. Issue 2 (April 2014) - Cockell, Charles S.; Cockell, Charles; Burchell, Mark; Martins, Zita
Abstract From a biological point of view, all environments in the Universe can be categorized into one of three types: uninhabitable, uninhabited habitat or inhabited habitat. This paper describes and defines different habitat types in the Universe with a special focus on environments not usually encountered on the Earth, but which might be common on other planetary bodies. They include uninhabited habitats, subtypes of which are sterile habitats and organic-free habitats. Examples of the different types of environments are provided with reference to the Eyjafjallajökull, Iceland. These habitat types are used to identify testable hypotheses on the abundance of different habitats and the distribution of life in the Universe.